Computational Thinking : Experiences of Rural Pupils in Sarawak Primary School - Nur Hasheena, Anuar (Universiti Malaysia Sarawak, (UNIMAS), 2021)
Computational thinking (CT) is one of the cognitive processes involved in STEM learning which human use in problem-solving to provide computational solutions that humans and machines can support. It has been denoted as a universal skill needed for everyone to learn in life, starting from a young age. However, computational thinking term and the underlying skills still poorly understood and underestimated by teachers and pupils, especially in isolated primary schools at Sarawak. The study aims to identify the effective pedagogical approaches in learning Computational Thinking skills and address the needs and challenges faced in implementing Computational Thinking in a rural primary school in Sarawak. It involved 22 participants with 11 boys and 11 girls of Primary 4 and Primary 5 originated from Miri, Sarawak. The samples were chosen through the purposive sampling method. The study employed embedded mixed methods design using a quasi-experimental approach which aims to provide an in-depth understanding of how pupils in remote rural area adapt and process to learning Computational Thinking skills (i.e., abstraction, algorithmic thinking, and decomposition) as well as their attitudes towards computational thinking practices by engaging in an unplugged game-based, art-based, Scratch programming and robotic activities through a revised Computational Thinking pedagogical model. The Computational Thinking results of quantitative data were collected using pre-test and post-test that consisted of five subjective computational thinking items. The descriptive statistics and statistical tests were run using IBM SPSS Statistics 25. The analysis of independent variables was performed using a parametric test of Independent Samples t-test. The qualitative data such as field observation, interview, reflective written responses, and researcher interpretation were qualitatively analysed. The findings indicate that learning new skills such as Computational Thinking skills (i.e., programming skill) is perceived as necessary by teachers and participants in rural school. Based on the qualitative and quantitative analysis of computational thinking pedagogical approaches, it can be concluded that computational thinking skills acquired through unplugged, art-integration, tinkering, making, remixing, and robotics approaches have been proven to be effective for primary school pupils at Sarawak at the primary level. Although the quantitative data does not show promising results, the qualitative data can be used to support the learning experiences and knowledge acquired from the learning activities proposed. Scaffold from adults and supportive peers are needed when learning computational thinking skills, especially for beginners. In conclusion, the results of the study provide positive and encouraging evidence on the "learning by doing" approach and the practicality of integrating computational thinking activities in rural schools can help rural school pupils develop Computational Thinking skills.